Pengembangan Media Komik Digital Keragaman Budaya untuk Meningkatkan Minat Belajar Siswa Kelas lV SD - Syifa Ainurrahmah; Marini, Arita; Hadi, Waluyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Abstrak Primary education is the foundation of character building of the nation. Cultural Diversity material for fourth grade elementary school students has high urgency, but conventional learning methods still result in low student learning interest. This study aims to develop a digital comic media based on cultural diversity that is valid, practical, and effective in improving the learning interest of fourth grade elementary school students. The method used is Research and Development with the 4D model consisting of Define, Design, Develop, and Disseminate stages (Thiagarajan et al., 1974). The digital comic was developed using the Canva platform and presents representations of cultural identity such as traditional houses, traditional clothing, regional dances, and traditional ceremonies from various provinces in Indonesia in story narratives close to students’ lives. Expert validation results showed very valid scores: content expert (87.5%) and media expert (90.0%). Practicality test results by teachers (89.0%) and students (86.5%) were in the very practical category. The Wilcoxon test showed a significant increase in student learning interest of 24.8% (p<0.05). It was concluded that the developed cultural diversity digital comic media is suitable for use as a learning medium in fourth grade elementary school and is able to serve as a humanistic educational instrument in instilling awareness of diversity.